The fall of a city: Refugees, exodus and exile in Ernest Hemingway’s Istanbul, 1922 - Maksudyan, Nazan (Journal of European studies, 2023)
Ernest Hemingway arrived in Istanbul on 30 September 1922 to cover the end of the Greek–Turkish War for the Toronto Star. From late October to mid-November 1922, Hemingway wrote 20 articles about the last days of the war and the re-constellation of political legitimacy in the region. There are four distinguishing features of Hemingway’s reports from Constantinople. First, they provided an eloquent depiction of the city, suggesting the charm and squalor of old ‘Constan’ for the young writer. The second was a clear expectation of a ‘second disaster’, which was assumed to be a replica of Smyrna. Hemingway clearly observed the fears of non-Muslims and foreigners in the city, who were panicking over possible new massacres and pillage. Third, Hemingway quickly realized that the exodus of people – the desperate flight of Christian refugees – and Turkification of the country would be his main subject. His repeated emphasis on refugees permanent loss of a home is reminiscent of Hannah Arendt’s famous essay ‘We Refugees’, as well as a precursor to Agamben’s point that refugees are reduced to ‘bare life’. Lastly, his prose relied on irony and cynicism, as a cover for his disappointment and shame for humanity and modern civilization. Juxtaposing his writing with contemporary local accounts, I intend to situate his witnessing into the larger historiography of ‘Armistice Istanbul’ and the homogenization policies of the winning Turkish nationalist leadership. Hemingway’s critique of (homogeneous) nation-state formation after the war and the favourable involvement of the Allied countries and humanitarian agencies in the mass production of refugees was quite exceptional and ahead of his times.